Analysis of Solid and Liquid Waste Characteristics of Tofu Industry in Bancar Village, Bungkal District, Ponorogo Regency - Nostia, Rohima; Kurniawan, Andi; Koderi (Postgraduate School of Universitas Brawijaya, 2023)
The tofu industry in Bancar village, Bungkal district, Ponorogo regency, East Java province is still at micro enterprise (MSME) level and is operated with simple technology, so the level of water and raw efficiency is high. Material consumption is still low and waste generation is relatively high. This study aims to analyze the solid and liquid waste characteristics of the tofu industry in Bancar Village, Bungkal District, Ponorogo Regency. To study this case, a sampling technique of solid and liquid waste was carried out and further testing was carried out in the laboratory. Based on the results of the research, the solid waste characteristics of the tofu industry contain moisture content of 93.18%; ash content of 0.21%; crude protein content of 2.77%; crude fiber content of 1.65%; carbohydrate content of 1.88%; calorie content of 21.48 Cal/100 gr. As for liquid waste, it characteristics has 5 parameters to be tested, namely Biological Oxygen Demand (BOD5) has a level of 869.7 mg/L, Chemical Oxygen Demand (COD) has a level of 4480 mg/L, Total Suspended Solid (TSS) has a level of 110 mg/L, and pH has a value of 3.95. Keywords: characteristics, tofu industry, solid waste, liquid waste